Pemanfaatan Jamur Tiram Putih (Pleurotus Ostreatus) Sebagai Biomaterial Konstruksi Militer Ramah Lingkungan - Aritonang, Sovian; C Lubis, Astrid Blandina; Ramadhanty, Chrisna Prawiradhiva; Hamidah, Fikriyah; Hutama, Raihansyah Raja (Fakultas Teknik UMSU, 2024)
Developments in the 21st century require the development of technology, one of which is construction material technology. The construction material generally used is conventional concrete on the market. However, in its use, conventional concrete is not environmentally friendly. Therefore, biomaterials were developed from the use of white oyster mushrooms with various media. This study of biomaterials develops mycelium using three types of media, namely rice husk waste, corn stalk waste and wood dust waste. The aim of this research is to obtain optimal media for the growth of white oyster mushrooms. The cellulose content of corn stalks, rice husks, and sawdust were 33%, 38%, and 41%, respectively. The research results showed that sawdust waste media was the best medium as a fungal growth medium. Wood dust waste with a cellulose content of 41% can produce the growth of mold as high as 8.62 cm. In rice husk waste media with a cellulose content of 38%, 5.62 cm was obtained. Then, on corn stalk waste media with a cellulose content of 33%, fungal growth was obtained as high as 0.632 cm